Environment Design as a Method of Modeling a Cultural Space of a City - Mukhametovna Makhmutova, Madina; Elvira Rstamovna, Yusupova; Zanfira Yagsupovna, Miskichekova (International Journal of Criminology and Sociology, 2022)
The relevance of the studied problem because the study of the subject-spatial environment of the city, a comprehensive solution of which involves not only summing up the ideas of culturologists, architects, urban planners, designers, psychologists, anthropologists, sociologists, but also designing and modeling the artificially created environment as a process of forming the cultural space of the city. The content of the socio-cultural being of a human form the ideological and thematic basis of the designer’s design plan. Modern environmental design, including an ethnic component, must correspond to the substantial and aesthetic characteristics of a particular regional culture. After the research work conducted by the authors of the cultural and artworks of scientists and specialists - designers, architects, we can argue that the design of the environment is a necessary component of the cultural image of the city. In this regard, there is a need for a comprehensive analysis of the factors of the formation of the cultural space, which becomes the basis for understanding the applied function of the designer’s activity, manifested in the decorative and ornamental nature of environment design objects. All components of the subject-spatial environment of the "Turkic-Tatar civilization" can be considered the basis of the design culture and as a result of the continuity of these traditions in modeling the cultural space of the city.